Negative plate, preparation method thereof and battery
By designing a three-layer active layer structure in the negative electrode sheet, using the combination of graphite and silicon-based materials, soft carbon and/or hard carbon, the problems of low conductivity and poor fast charging capabilities of the silicon-based materials are solved, and the high energy density, excellent fast charging and cycling performance of the battery cell are achieved.
Patent Information
- Application Number
- CN202510088507.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-29
AI Technical Summary
The silicon-based materials have poor conductivity in the negative electrode sheet and the slow migration speed of active ions, which leads to poor fast charging capabilities of secondary batteries, limiting the application of silicon-based materials in the negative electrode sheet.
A negative electrode sheet is designed, and the active layer consists of three layers: the first active layer consists of graphite and silicon-based material, the second active layer consists of soft carbon and/or hard carbon, and the third active layer consists of graphite. With this laminated structure, the conductivity and fast charging capability of the negative electrode sheet are improved.
While ensuring the energy density of the battery cell, it can improve the cycling performance and fast charging performance of the battery cell, avoid interlayer lithium evolution and improve the overall performance of the negative electrode sheet.
Smart Images

Figure CN119905519A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a negative electrode sheet and a preparation method thereof, and a battery. Background Art
[0002] In the field of new energy vehicles, improving the energy density of battery cells is the key to improving endurance. Silicon-based materials have a higher gram capacity than graphite. Currently, applying silicon-based materials in negative electrode sheets is an important method to improve the energy density of battery cells.
[0003] However, the conductivity of silicon-based materials is poor, and the migration of active ions (such as lithium ions or sodium ions) in the silicon-based material system is slow. Therefore, the negative electrode sheets containing silicon-based materials will result in poor fast charging capabilities of secondary batteries, which limits the application of negative electrode sheets containing silicon-based materials in secondary batteries. Summary of the invention
[0004] In view of this, the embodiments of the present application provide a negative electrode sheet, a preparation method thereof, and a battery to solve at least one problem existing in the background technology.
[0005] In a first aspect, an embodiment of the present application provides a negative electrode sheet, comprising:
[0006] current collector;
[0007] An active layer, disposed on at least one side surface of the current collector, the active layer comprising a first active layer, a second active layer and a third active layer sequentially stacked on the current collector;
[0008] The material of the first active layer includes graphite and silicon-based material, the material of the second active layer includes soft carbon and / or hard carbon, and the material of the third active layer includes graphite.
[0009] In conjunction with the first aspect of the present application, in an optional embodiment, the material of the first active layer further includes a first binder, the material of the second active layer further includes a second binder, and the material of the third active layer further includes a third binder; the negative electrode sheet satisfies at least one of the following characteristics:
[0010] (1) The first binder includes at least two of sodium carboxymethyl cellulose, styrene-butadiene rubber, and polyacrylic acid binders;
[0011] (2) the second binder comprises at least two of sodium carboxymethyl cellulose, styrene-butadiene rubber, and polyacrylic acid binders;
[0012] (3) The third binder includes at least two of sodium carboxymethyl cellulose, styrene-butadiene rubber, and polyacrylic acid binders;
[0013] (4) The mass percentage of the first binder in the first active layer is 2.5% to 10%;
[0014] (5) The mass percentage of the second binder in the second active layer is 2% to 6%;
[0015] (6) The mass proportion of the third binder in the third active layer is 1.5% to 3%.
[0016] In conjunction with the first aspect of the present application, in an optional embodiment, the material of the first active layer further includes a first conductive agent, the material of the second active layer further includes a second conductive agent, and the material of the third active layer further includes a third conductive agent; the negative electrode sheet satisfies at least one of the following characteristics:
[0017] (1) The first conductive agent includes at least one of carbon black, carbon nanotubes, graphene, and acetylene black;
[0018] (2) the second conductive agent includes at least one of carbon black, carbon nanotubes, graphene, and acetylene black;
[0019] (3) The third conductive agent includes at least one of carbon black, carbon nanotubes, graphene, and acetylene black;
[0020] (4) the mass proportion of the first conductive agent in the first active layer is greater than the mass proportion of the second conductive agent in the second active layer, and greater than the mass proportion of the third conductive agent in the third active layer;
[0021] (5) The mass proportion of the second conductive agent in the second active layer is greater than the mass proportion of the third conductive agent in the third active layer.
[0022] In conjunction with the first aspect of the present application, in an optional embodiment, the negative electrode sheet satisfies at least one of the following characteristics:
[0023] (1) The silicon-based material includes at least one of silicon dioxide, silicon carbon, and silicon;
[0024] (2) In the first active layer, the mass proportion of the silicon-based material in the mixture of the graphite and the silicon-based material is greater than 0 and less than or equal to 90%;
[0025] (3) The surface density of the negative electrode sheet is 4.54 mg / cm 2 ~12.34mg / cm 2 ;
[0026] (4) The thickness of the first active layer is 10 μm to 70 μm;
[0027] (5) The thickness of the second active layer is 5 μm to 20 μm;
[0028] (6) The thickness of the third active layer is 8 μm to 40 μm.
[0029] In a second aspect, an embodiment of the present application provides a method for preparing a negative electrode sheet, comprising the following steps:
[0030] S1: preparing a first slurry, a second slurry and a third slurry, wherein the first slurry comprises a first active material, the first active material comprises graphite and a silicon-based material, the second slurry comprises a second active material, the second active material comprises soft carbon and / or hard carbon, and the third slurry comprises a third active material, the third active material comprises graphite;
[0031] S2: coating the first slurry, the second slurry and the third slurry on at least one side surface of the current collector, and drying to obtain a first active layer, a second active layer and a third active layer sequentially stacked on the current collector; the material of the first active layer includes the first active material, the material of the second active layer includes the second active material, and the material of the third active layer includes the third active material.
[0032] In combination with the second aspect of the present application, in an optional embodiment, the mass proportion of the silicon-based material in the first active material is greater than 0 and less than or equal to 90; and / or, the silicon-based material includes at least one of silicon monoxide, silicon carbon, and silicon.
[0033] In conjunction with the second aspect of the present application, in an optional embodiment, preparing the first slurry in step S1 includes:
[0034] The first active material, the first binder and the first conductive agent are mixed to prepare the first slurry; the mass ratio of the first active material, the first binder and the first conductive agent is (85-97): (2-10): (1-5).
[0035] In conjunction with the second aspect of the present application, in an optional embodiment, preparing the second slurry in step S1 includes:
[0036] The second active material, the second binder and the second conductive agent are mixed to prepare the second slurry; the mass ratio of the second active material, the second binder and the second conductive agent is (96-98): (1.5-3): (0.5-1).
[0037] In conjunction with the second aspect of the present application, in an optional embodiment, the preparing the third slurry in step S1 includes:
[0038] The third active material, the third binder and the third conductive agent are mixed to prepare the third slurry; the mass ratio of the third active material, the third binder and the third conductive agent is (96-98): (1.5-3): (0.5-1).
[0039] In a third aspect, an embodiment of the present application provides a battery, comprising the negative electrode sheet described in any one of the first aspect or the negative electrode sheet prepared by the preparation method described in any one of the second aspect.
[0040] Compared with the prior art, the embodiments of the present application have the following beneficial effects:
[0041] The negative electrode sheet, preparation method thereof and battery provided in the embodiments of the present application, the negative electrode sheet comprises: a current collector; an active layer, arranged on at least one side surface of the current collector, the active layer comprising a first active layer, a second active layer and a third active layer sequentially stacked on the current collector; the material of the first active layer comprises graphite and silicon-based material, the material of the second active layer comprises soft carbon and / or hard carbon, and the material of the third active layer comprises graphite. In the embodiment of the present application, the active layer in the negative electrode sheet is three layers, the first active layer includes graphite and silicon-based materials, which can exert a higher gram capacity, and the third active layer includes graphite with high conductivity, has a higher fast charging capability, and is conducive to forming a stable and dense solid electrolyte interface film at the interface between the negative electrode sheet and the electrolyte to ensure the cycle performance of the battery. By arranging a second active layer including soft carbon and / or hard carbon between the first active layer and the third active layer, due to the large interlayer spacing between the soft carbon and / or hard carbon, the active ions (such as lithium ions or sodium ions) are embedded and released in the soft carbon and / or hard carbon at a fast speed, so that the second active layer can be used as a fast ion conductor layer, which is convenient for active ion transmission and avoids the interlayer lithium precipitation phenomenon between the first active layer and the second active layer, thereby ensuring the energy density of the battery cell while improving the cycle performance and fast charging performance of the battery cell.
[0042] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0044] Figure 1 A schematic diagram of the cross-sectional structure of a negative electrode sheet provided in an embodiment of the present application;
[0045] Figure 2 A schematic flow chart of a method for preparing a negative electrode sheet provided in an embodiment of the present application. DETAILED DESCRIPTION
[0046] In order to make the technical scheme and beneficial effects of the present invention more obvious and easy to understand, the following is described in detail by combining the accompanying drawings and listing specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually based on conventional experimental conditions. The reagents and raw materials used in the present invention are commercially available unless otherwise specified.
[0047] In the following description, a large number of specific details are given to provide a more thorough understanding of the present application. However, it is obvious to those skilled in the art that the present application can be implemented without one or more of these details. In other examples, in order to avoid confusion with the present application, some technical features known in the art are not described; that is, all features of the actual embodiments are not described here, and well-known functions and steps are not described in detail.
[0048] The purpose of the terms used herein is only to describe specific embodiments and is not intended to be limiting of the present application. When used herein, the singular forms "one", "an" and "said / the" are also intended to include plural forms, unless the context clearly indicates otherwise. It should also be understood that the terms "consisting of" and / or "comprising", when used in this specification, determine the presence of the features, integers, steps, operations, elements and / or parts, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, parts and / or groups. When used herein, the term "and / or" includes any and all combinations of the relevant listed items.
[0049] In order to thoroughly understand the present application, detailed steps and detailed structures will be presented in the following description to illustrate the technical solution of the present application. The preferred embodiments of the present application are described in detail below, but in addition to these detailed descriptions, the present application may also have other implementation methods.
[0050] Unless otherwise defined, technical and scientific terms used in this application have the same meanings as those in the technical field to which this application belongs.
[0051] If no specific techniques or conditions are specified in the following examples, the conventional techniques or conditions described in the literature in the art, or the conditions recommended by the product instructions and the manufacturer are generally used. The numerical ranges in the following examples all include the endpoint values.
[0052] The present application embodiment provides a negative electrode sheet, such as Figure 1As shown, the negative electrode sheet includes: a current collector 100; an active layer 200, which is arranged on at least one side surface of the current collector 100, and the active layer 200 includes a first active layer 201, a second active layer 202 and a third active layer 203 stacked in sequence on the current collector 100; the material of the first active layer 201 includes graphite and silicon-based materials, the material of the second active layer 202 includes soft carbon and / or hard carbon, and the material of the third active layer 203 includes graphite.
[0053] In the negative electrode sheet of the embodiment of the present application, the first active layer 201 includes graphite and silicon-based materials, which can exert a higher gram capacity. The third active layer 203 includes graphite with high conductivity, has a higher fast charging capability, and is conducive to forming a stable and dense solid electrolyte interface film at the interface between the negative electrode sheet and the electrolyte to ensure the cycle performance of the battery. By arranging a second active layer 202 including soft carbon and / or hard carbon between the first active layer 201 and the third active layer 203, due to the large interlayer spacing between the soft carbon and / or hard carbon, the active ions are embedded and released from the soft carbon and / or hard carbon at a fast speed, so that the second active layer 202 can be used as a fast ion conductor layer to facilitate the transmission of active ions and avoid the interlayer lithium precipitation phenomenon between the first active layer 201 and the second active layer 202, thereby ensuring the energy density of the battery cell while improving the cycle performance and fast charging performance of the battery cell.
[0054] Understandably, Figure 1 The active layer 200 being located on one side surface of the current collector 100 is only an example. In some specific embodiments, the active layer 200 may be located on multiple side surfaces of the current collector 100. For example, the active layer 200 may be located on two opposite side surfaces of the current collector 100.
[0055] For example, the silicon-based material may include at least one of silicon oxide, silicon carbon, and silicon. The graphite in the first active layer 201 and / or the third active layer 203 may include at least one of artificial graphite, natural graphite, and modified graphite.
[0056] In some embodiments, in the first active layer 201, the mass proportion of the silicon-based material in the mixture of graphite and silicon-based material is greater than 0 and less than or equal to 90%, for example, it can be 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90% or any value between any two of the above numerical ranges. In this way, the gram capacity and conductivity of the first active layer 201 can be taken into account.
[0057] In some embodiments, the thickness of the first active layer 201 may be 10 μm to 70 μm, for example, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm or any value between any two of the above ranges. In this way, the first active layer 201 can better play the role of increasing the gram capacity of the negative electrode sheet, thereby further increasing the energy density of the battery cell.
[0058] In a specific embodiment, the ratio of the thickness of the first active layer 201 to the thickness of the active layer 200 may be greater than or equal to 1 / 2 and less than 1. This ensures that the first active layer 201 has a sufficient proportion in the active layer 200, thereby better ensuring the energy density of the battery cell.
[0059] In some embodiments, the thickness of the second active layer 202 may be 5 μm to 20 μm, for example, 5 μm, 10 μm, 15 μm, 20 μm, or any value between any two of the above ranges. This makes it easier for the second active layer 202 to adjust the transmission of active ions, thereby better avoiding the problem of interlayer lithium deposition between the first active layer 201 and the second active layer 202, thereby further improving the cycle performance of the battery cell.
[0060] Since the gram capacity of hard carbon and / or soft carbon is lower than that of silicon-based materials, when the thickness of the second active layer 202 is too thick, the surface capacity of the negative electrode sheet will be reduced, which will affect the energy density of the battery cell; and when the thickness of the second active layer 202 is too small, the improvement effect on the active ion transport is weak, and the effect on improving the fast charging performance and cycle performance of the battery cell is limited; therefore, in a specific embodiment, the ratio of the thickness of the second active layer 202 to the thickness of the active layer 200 can be greater than 0 and less than 1 / 4. In this way, the energy density, fast charging performance and cycle performance of the battery cell can be better taken into account.
[0061] In some embodiments, the thickness of the third active layer 203 may be 8 μm to 40 μm, for example, 8 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, or any value between any two of the above ranges. In this way, the third active layer 203 can further improve the fast charging performance and cycle performance of the battery cell.
[0062] In some embodiments, the surface density of the negative electrode sheet can be 4.54 mg / cm 2 ~12.34mg / cm 2 This can make the negative electrode sheet have a higher gram capacity and can better improve the fast charging performance and cycle performance of the battery cell.
[0063] In some embodiments, the material of the first active layer 201 may further include a first binder, the material of the second active layer 202 may further include a second binder, and the material of the third active layer 203 may further include a third binder.
[0064] Exemplarily, the first binder, the second binder, and the third binder may each independently include at least two of sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), and polyacrylic acid binders; wherein the polyacrylic acid binder may include polyacrylic acid (PAA) or lithium polyacrylate (PAA-Li), etc. The first binder, the second binder, and the third binder may be the same or different, and may be combined by selecting a suitable binder type according to actual needs.
[0065] In the embodiment of the present application, the binders in the first active layer 201, the second active layer 202 and the third active layer 203 include more than two types, so that the materials in each active layer can be more evenly dispersed and tightly connected, while increasing the connection stability between the active layer 200 and the current collector 100 and between adjacent layers in the active layer 200, thereby improving the negative electrode sheet peeling strength and electrochemical performance.
[0066] In some embodiments, the mass percentage of the first binder in the first active layer 201 can be 2.5% to 10%, for example, 2.5%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or any value between any two of the above numerical ranges.
[0067] In some embodiments, the mass percentage of the second binder in the second active layer 202 may be 2% to 6%, for example, 2%, 3%, 4%, 5%, 6% or any value between any two of the above ranges.
[0068] In some embodiments, the mass proportion of the third binder in the third active layer 203 may be 1.5% to 3%, for example, 1.5%, 2%, 2.5%, 3% or any value between any two of the above ranges.
[0069] By controlling the mass proportions of the first binder, the second binder and the third binder in the active layer in which they are located within the above range, it is possible to avoid the influence of excessive addition of binder on the energy density of the battery cell while ensuring that the binder can better exert its bonding performance.
[0070] In some embodiments, the material of the first active layer 201 may further include a first conductive agent, the material of the second active layer 202 may further include a second conductive agent, and the material of the third active layer 203 may further include a third conductive agent.
[0071] The conductive agent in the first active layer 201, the second active layer 202 and the third active layer 203 can ensure that the negative electrode sheet has better conductivity, thereby reducing the resistance of the negative electrode sheet and further improving the performance of the battery. Exemplarily, the first conductive agent, the second conductive agent and the third conductive agent can each independently include at least one of carbon black, carbon nanotubes, graphene and acetylene black. The first conductive agent, the second conductive agent and the third conductive agent can be the same or different, and the appropriate type of conductive agent can be selected according to actual needs.
[0072] The negative electrode sheet in the embodiment of the present application constructs a fast ion conductor layer (second active layer 202) between the composite layer of silicon-based material and graphite material (first active layer 201) and the graphite layer (third active layer 203). On the one hand, it can improve the fast charging ability of the battery cell corresponding to the negative electrode sheet of the silicon-based material and graphite mixed system. At the same time, it can solve the problem of easy lithium precipitation between the active layer containing graphite and silicon-based materials and the active layer containing graphite, and solve the lithium precipitation caused by different kinetic properties between different graphite layers in the negative electrode sheet, which can effectively improve the cycle performance of the battery cell. Under the premise of ensuring the energy density of the battery cell, the battery cell has excellent fast charging performance and cycle performance.
[0073] The present application also provides a method for preparing a negative electrode sheet. Figure 2 The method for preparing the negative electrode sheet provided in the embodiment of the present application comprises the following steps:
[0074] S1: preparing a first slurry, a second slurry and a third slurry, wherein the first slurry includes a first active material, the first active material includes graphite and a silicon-based material, the second slurry includes a second active material, the second active material includes soft carbon and / or hard carbon, and the third slurry includes a third active material, the third active material includes graphite;
[0075] S2: coating the first slurry, the second slurry and the third slurry on at least one side surface of the current collector, and drying to obtain a first active layer, a second active layer and a third active layer stacked on the current collector in sequence; the material of the first active layer includes the first active material, the material of the second active layer includes the second active material, and the material of the third active layer includes the third active material.
[0076] In the embodiment of the present application, a first active layer, a second active layer and a third active layer stacked in sequence on the current collector are formed by coating a first slurry, a second slurry and a third slurry on the current collector, and the preparation method is simple; the first active layer includes graphite and silicon-based materials, which can exert a higher gram capacity, and the third active layer includes graphite with high conductivity, has a higher fast charging capability, and is conducive to forming a stable and dense solid electrolyte interface film at the interface between the negative electrode sheet and the electrolyte to ensure the cycle performance of the battery, and a second active layer including soft carbon and / or hard carbon is formed between the first active layer and the third active layer. Due to the large interlayer spacing between the soft carbon and / or hard carbon, the active ions are embedded and released from the soft carbon and / or hard carbon at a fast speed, so that the second active layer can be used as a fast ion conductor layer, which is convenient for active ion transmission and avoids interlayer lithium precipitation between the first active layer and the second active layer, thereby ensuring the energy density of the battery cell while improving the cycle performance and fast charging performance of the battery cell.
[0077] The preparation of the first slurry in step S1 may include: mixing the first active material, the first binder and the first conductive agent to prepare the first slurry; the mass ratio of the first active material, the first binder and the first conductive agent may be (85-97): (2-10): (1-5), for example, 85:2:1, 90:5:2, 95:8:4, 97:10:5 or any other mass ratio within the above mass ratio range. In this way, the gram capacity, conductive properties and mechanical properties of the first active layer prepared can be at a relatively good level.
[0078] In some embodiments, the mass proportion of the silicon-based material in the first active material can be greater than 0 and less than or equal to 90, for example, it can be 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90% or any value between any two of the above numerical ranges. In this way, the gram capacity and conductivity of the prepared first active layer can be taken into account. Exemplarily, the silicon-based material can include at least one of silicon oxide, silicon carbon, and silicon.
[0079] The preparation of the second slurry in step S1 may include: mixing the second active material, the second binder and the second conductive agent to prepare the second slurry; the mass ratio of the second active material, the second binder and the second conductive agent may be (96-98): (1.5-3): (0.5-1), for example, 96:1.5:0.5, 97:2:0.7, 98:3:1 or any other mass ratio within the above mass ratio range. In this way, the gram capacity, conductive properties and mechanical properties of the prepared second active layer can be at a relatively good level.
[0080] The preparation of the third slurry in step S1 may include: mixing the third active material, the third binder and the third conductive agent to prepare the third slurry; the mass ratio of the third active material, the third binder and the third conductive agent may be (96-98): (1.5-3): (0.5-1), for example, 96:1.5:0.5, 97:2:0.7, 98:3:1 or any other mass ratio within the above mass ratio range. In this way, the gram capacity, conductive properties and mechanical properties of the prepared third active layer are all at a relatively good level.
[0081] Exemplarily, the first binder, the second binder and the third binder in step S1 may each independently include at least two of sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), and polyacrylic binders. The first conductive agent, the second conductive agent and the third conductive agent in step S1 may each independently include at least one of carbon black, carbon nanotubes, graphene, and acetylene black. The solvent for preparing the first slurry, the second slurry, and the third slurry in step S1 may all include water, such as deionized water.
[0082] In some embodiments, in step S2, the step of coating the first slurry, the second slurry and the third slurry on at least one side of the current collector may include: using a three-layer coating die head, coating the first slurry, the second slurry and the third slurry on the current collector at the same time, and obtaining the negative electrode sheet after drying. This makes it easy to control the coating amount and uniformity of each layer of slurry and improve the overall coating quality, and can greatly improve production efficiency and reduce costs.
[0083] Of course, the present application does not exclude the use of a single-layer coating die head to sequentially coat the first slurry, the second slurry, and the third slurry on at least one side of the current collector. For example, first, the first slurry is coated on at least one side of the current collector, and after drying, the first active layer is formed; then, the second slurry is coated on the first active layer, and after drying, the second active layer is formed; then, the third slurry is coated on the second active layer, and after drying, the third active layer is formed.
[0084] Since the first active material in the first slurry includes graphite and silicon-based materials, the first active layer formed by the first slurry has a greater influence on the gram capacity of the negative electrode sheet. By controlling the weight proportion of the first slurry in the overall slurry composed of the first slurry, the second slurry and the third slurry, the energy density of the battery cell can be better controlled. In a specific embodiment, the ratio of the weight of the first slurry to the total weight of the first slurry, the second slurry and the third slurry can be greater than or equal to 1 / 2 and less than 1. In this way, the energy density of the battery cell can be better guaranteed.
[0085] The second active layer formed by the second slurry can be used as a fast ion conductor layer to facilitate the transmission of active ions. However, since the second active material in the second slurry includes hard carbon and / or soft carbon, the gram capacity of the second active layer is lower than that of the first active layer. By controlling the weight proportion of the second slurry in the overall slurry composed of the first slurry, the second slurry and the third slurry, the fast charging performance and cycle performance of the battery cell can be improved while minimizing the impact on the energy density of the battery cell. In a specific embodiment, the ratio of the weight of the second slurry to the total weight of the first slurry, the second slurry and the third slurry can be greater than 0 and less than 1 / 4. In this way, the energy density, fast charging performance and cycle performance of the battery cell can be better taken into account.
[0086] In the actual preparation process, the weight (coating weight) of the first slurry, the second slurry and the third slurry can be controlled by controlling coating parameters, such as gasket thickness, chamber pressure of the coating equipment, etc. Specifically, the control can be carried out using a process well known to those skilled in the art, which will not be described in detail here.
[0087] In the process of simultaneously coating the first slurry, the second slurry and the third slurry on the current collector using a three-layer coating die head, the binder and the conductive agent in the lower slurry will float. Therefore, in one specific embodiment, the mass proportion of the first binder in the first slurry can be greater than the mass proportion of the second binder in the second slurry, and greater than the mass proportion of the third binder in the third slurry. In another specific embodiment, the mass proportion of the second binder in the second slurry can be greater than the mass proportion of the third binder in the third slurry. In this way, it is conducive to promoting the uniform distribution of the binder in the different active layers finally formed, and the use of the binder can be reduced while ensuring the peeling strength of the negative electrode sheet, and the content of the active material in the active layer can be further increased, so that the energy density of the battery cell can be further improved, so that the overall performance of the battery cell is higher.
[0088] In a more specific embodiment, the mass proportion of the first binder in the first slurry is greater than the mass proportion of the second binder in the second slurry, and the mass proportion of the second binder in the second slurry is greater than the mass proportion of the third binder in the third slurry. This is conducive to promoting a more uniform distribution of the binders in the different active layers finally formed, and can further increase the content of active materials in the active layer while ensuring the peel strength of the negative electrode sheet, thereby further improving the energy density of the battery cell.
[0089] In one specific embodiment, the mass proportion of the first conductive agent in the first slurry may be greater than the mass proportion of the second conductive agent in the second slurry, and greater than the mass proportion of the third conductive agent in the third slurry. In another specific embodiment, the mass proportion of the second conductive agent in the second slurry may be greater than the mass proportion of the third conductive agent in the third slurry. In this way, it is conducive to promoting the uniform distribution of the conductive agent in the different active layers finally formed, and the content of the active material in the active layer can be further increased while ensuring the conductivity of the negative electrode sheet, thereby further improving the energy density of the battery cell, making the overall performance of the battery cell higher.
[0090] In a more specific embodiment, the mass proportion of the first conductive agent in the first slurry is greater than the mass proportion of the second conductive agent in the second slurry, and the mass proportion of the second conductive agent in the second slurry is greater than the mass proportion of the third conductive agent in the third slurry. This is conducive to promoting a more uniform distribution of the conductive agent in the different active layers finally formed, and can reduce the use of the conductive agent while ensuring the conductivity of the negative electrode sheet, and further increase the content of the active material in the active layer, thereby further improving the energy density of the battery cell.
[0091] In some embodiments, the thickness of the first active layer formed in step S2 may be 10 μm to 70 μm, for example, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, or any value between any two of the above ranges. In this way, the first active layer can better play a role in increasing the gram capacity of the negative electrode sheet, thereby further increasing the energy density of the battery cell.
[0092] In some embodiments, the thickness of the second active layer formed in step S2 may be 5 μm to 20 μm, for example, 5 μm, 10 μm, 15 μm, 20 μm, or any value between any two of the above ranges. This makes it easier for the second active layer to adjust the transmission of active ions, thereby better avoiding the problem of interlayer lithium deposition between the first active layer and the second active layer, thereby further improving the cycle performance of the battery cell.
[0093] In some embodiments, the thickness of the third active layer formed in step S2 may be 8 μm to 40 μm, for example, 8 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, or any value between any two of the above ranges. In this way, the fast charging performance and cycle performance of the battery cell can be further improved through the third active layer.
[0094] In some embodiments, the surface density of the negative electrode sheet prepared in step S2 can be 4.54 mg / cm 2 ~12.34mg / cm 2This can make the negative electrode sheet have a higher gram capacity and can better improve the fast charging performance and cycle performance of the battery cell.
[0095] An embodiment of the present application further provides a battery, which includes the negative electrode sheet described in any of the above embodiments or the negative electrode sheet prepared by the preparation method described in any of the above embodiments.
[0096] It should be understood that since the battery in the embodiment of the present application includes the negative electrode sheet described in any of the above embodiments or includes the negative electrode sheet prepared by the preparation method described in any of the above embodiments, the beneficial effects of the negative electrode sheet in the above embodiments are applicable to the battery. The battery in the embodiment of the present application has high energy density, high cycle performance and high fast charging performance.
[0097] In some embodiments, the battery may be a secondary battery, and the secondary battery may be, for example, a lithium-ion battery or a sodium-ion battery. Typically, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. During the battery charge and discharge process, active ions are embedded and extracted back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays a role in conducting active ions between the positive electrode sheet and the negative electrode sheet. The separator is disposed between the positive electrode sheet and the negative electrode sheet, and mainly plays a role in preventing the positive and negative electrodes from short-circuiting, while allowing active ions to pass through.
[0098] In the actual preparation process of the battery, first, the positive electrode sheet, the separator, the negative electrode sheet, and the separator can be stacked in sequence, and a bare cell can be obtained after assembly. The assembly method can be, for example, a stacking method or a winding method; then, the electrolyte is injected into the dried bare cell, and a secondary battery is obtained after formation and aging. The negative electrode sheet is the negative electrode sheet described in any of the above embodiments or the negative electrode sheet prepared by the preparation method described in any of the above embodiments. The positive electrode sheet includes a positive electrode current collector (specifically, for example, aluminum foil) and a positive electrode active layer coated on the positive electrode current collector. Specifically, the positive electrode active layer may include a positive electrode active material, a conductive agent, and a binder, wherein the positive electrode active material may include, for example, at least one of lithium iron phosphate, lithium manganese iron phosphate, lithium nickel cobalt manganese oxide, and lithium nickel cobalt manganese aluminum oxide; the conductive agent may include, for example, at least one of conductive carbon black, carbon nanotubes, and acetylene black; the binder may include, for example, polyvinylidene fluoride (PVDF). The separator may be, for example, a polyethylene film, a polypropylene film, a polyvinylidene fluoride film, or a non-woven fabric. The electrolyte may include, for example, a lithium salt and a solvent or a sodium salt and a solvent, wherein the types of the lithium salt, sodium salt and solvent are not specifically limited and may be selected according to actual needs.
[0099] The technical solution of the present application is further described below in combination with a plurality of embodiments and comparative examples.
[0100] Example 1
[0101] The preparation of the negative electrode sheet in this embodiment includes the following steps:
[0102] Step S101: Graphite, silicon oxide material, conductive carbon black (super-P), sodium carboxymethyl cellulose (CMC) and polyacrylic acid (PAA) are mixed in a mass ratio of 76:19:1.5:1:2.5, and deionized water is added and stirred to form a first slurry that is uniformly mixed and stable; wherein the graphite and silicon oxide material are used as the first active material, super-P is used as the first conductive agent, and CMC and PAA are used as the first binder;
[0103] Step S102: After mixing hard carbon, super-P, CMC and PAA in a mass ratio of 97:0.8:0.8:1.4, deionized water is added and stirred to form a second slurry that is uniformly mixed and stable; wherein the hard carbon is used as the second active material, the super-P is used as the second conductive agent, and the CMC and PAA are used as the second binder;
[0104] Step S103: After mixing graphite, super-P, CMC and PAA in a mass ratio of 97.4:0.6:0.8:1.2, deionized water is added and stirred to form a third slurry that is uniformly mixed and stable; wherein graphite is used as the third active material, super-P is used as the third conductive agent, and CMC and PAA are used as the third binder;
[0105] Step S201: Use a three-layer coating die head to uniformly coat the first slurry, the second slurry and the third slurry prepared in the above steps S101 to S103 on the negative electrode collector copper foil at the same time, wherein the first slurry, the second slurry and the third slurry are stacked in sequence on the surface of the negative electrode collector, and the mass ratio of the first slurry, the second slurry and the third slurry is 1 / 2:1 / 6:1 / 3, and the negative electrode sheet is obtained after drying and cold pressing.
[0106] Comparative Example 1
[0107] The preparation of the negative electrode sheet in this comparative example includes the following steps:
[0108] Step S301: Graphite, silicon oxide material, super-P, CMC and PAA are mixed in a mass ratio of 86.4:9.6:1.5:0.9:1.6, and deionized water is added and stirred to form a uniformly mixed and stable negative electrode slurry;
[0109] Step S302: evenly coating the negative electrode slurry obtained in step S301 on the negative electrode current collector copper foil, drying and cold pressing to obtain a negative electrode sheet.
[0110] It should be noted that the surface density of the negative electrode sheets prepared in Example 1 and Comparative Example 1 is 9.74 mg / cm 2The silicon content per unit area of the negative electrode sheet of comparative example 1 is the same as that of the negative electrode sheet of embodiment 1, except that comparative example 1 is only subjected to single-layer coating.
[0111] Comparative Example 2
[0112] Step S401: Graphite, silicon oxide material, conductive carbon black (super-P), sodium carboxymethyl cellulose (CMC) and polyacrylic acid (PAA) are mixed in a mass ratio of 76:19:1.5:1:2.5, and deionized water is added and stirred to form a first slurry that is uniformly mixed and stable; wherein graphite and silicon oxide material are used as active materials, super-P is used as a conductive agent, and CMC and PAA are used as binders;
[0113] Step S402: Graphite, super-P, CMC and PAA are mixed in a mass ratio of 97.4:0.6:0.8:1.2, and deionized water is added and stirred to form a second slurry that is uniformly mixed and stable; wherein graphite is used as an active material, super-P is used as a conductive agent, and CMC and PAA are used as binders;
[0114] Step S403: Use a double-layer coating die to uniformly coat the first slurry and the second slurry prepared in the above steps S401 and S402 on the negative electrode current collector copper foil at the same time, wherein the first slurry and the second slurry are sequentially stacked on the surface of the negative electrode current collector, and the mass ratio of the first slurry to the second slurry is 1:1, and the negative electrode sheet is obtained after drying and cold pressing.
[0115] Comparative Example 3
[0116] Step S501: Graphite, silicon oxide material, conductive carbon black (super-P), sodium carboxymethyl cellulose (CMC) and polyacrylic acid (PAA) are mixed in a mass ratio of 76:19:1.5:1:2.5, and deionized water is added and stirred to form a first slurry that is uniformly mixed and stable; wherein graphite and silicon oxide material are used as active materials, super-P is used as a conductive agent, and CMC and PAA are used as binders;
[0117] Step S502: Graphite: hard carbon, super-P, CMC and PAA are mixed in a mass ratio of 65:32.4:0.6:0.8:1.2, and deionized water is added and stirred to form a second slurry that is mixed evenly and stably; wherein graphite is used as an active material, super-P is used as a conductive agent, and CMC and PAA are used as binders;
[0118] Step S503: Use a double-layer coating die to uniformly coat the first slurry and the second slurry prepared in the above steps S501 and S502 on the negative electrode current collector copper foil at the same time, wherein the first slurry and the second slurry are sequentially stacked on the surface of the negative electrode current collector, and the mass ratio of the first slurry to the second slurry is 1:1, and the negative electrode sheet is obtained after drying and cold pressing.
[0119] Comparative Example 4
[0120] Step S601: Graphite, silicon oxide material, conductive carbon black (super-P), sodium carboxymethyl cellulose (CMC) and polyacrylic acid (PAA) are mixed in a mass ratio of 76:19:1.5:1:2.5, and deionized water is added and stirred to form a first slurry that is uniformly mixed and stable; wherein graphite and silicon oxide material are used as active materials, super-P is used as a conductive agent, and CMC and PAA are used as binders;
[0121] Step S602: After mixing graphite, super-P, CMC and PAA in a mass ratio of 97.4:0.6:0.8:1.2, deionized water is added and stirred to form a second slurry that is uniformly mixed and stable; wherein graphite is used as an active material, super-P is used as a conductive agent, and CMC and PAA are used as binders;
[0122] Step S603: after mixing hard carbon, super-P, CMC and PAA in a mass ratio of 97:0.8:0.8:1.4, add deionized water and stir to form a third slurry that is mixed evenly and stably; wherein hard carbon is used as an active material, super-P is used as a conductive agent, and CMC and PAA are used as binders;
[0123] Step S604: using a three-layer coating die head to uniformly coat the first slurry, the second slurry and the third slurry prepared in the above steps S601 to S603 on the negative electrode current collector copper foil at the same time, wherein the first slurry, the second slurry and the third slurry are sequentially stacked on the surface of the negative electrode current collector, and the mass ratio of the first slurry, the second slurry and the third slurry is 1 / 2:1 / 3:1 / 6, and the negative electrode sheet is obtained after drying and cold pressing.
[0124] The negative electrode sheets obtained in the above-mentioned embodiments and comparative examples were prepared into batteries to test the electrochemical performance of the batteries.
[0125] The preparation steps of the battery are as follows: the positive electrode active material (NCM), the conductive agent (super-P) and the binder (PVDF) are mixed in a mass ratio of 98%:1%:1%, NMP is added and stirred to form a uniformly mixed and stable positive electrode slurry, the positive electrode slurry is uniformly coated on the positive electrode collector, and the positive electrode sheet is obtained after drying and cold pressing; the negative electrode sheet is the negative electrode sheet prepared in the above embodiment and comparative example; the diaphragm is a polypropylene film; the electrolyte is LiPF6 Solution of LiPF dissolved in a mixed solvent of ethylene carbonate, ethyl methyl carbonate and diethyl carbonate (the volume ratio of ethylene carbonate, ethyl methyl carbonate and diethyl carbonate is 1:1:1). 6 The concentration is 1.2 mol / L. The positive electrode sheet, separator, negative electrode sheet, and separator are stacked in sequence, and wound to form a battery core. Then, the electrolyte is injected into the dry battery core, and a lithium-ion battery is obtained after formation and aging.
[0126] The test methods for the fast charging capability and cycle performance of the battery are as follows:
[0127] (1) Fast charging performance test: By implanting three electrodes, test the maximum fast charging capability of 10% to 80% SOC (State of Charge) when the potential of the negative electrode relative to the reference electrode is greater than 0V. Specifically: adjust the battery charge to 10% SOC, and the initial charging rate is set to 3.5C. When the potential of the negative electrode relative to the reference electrode is lower than 0V, reduce the current to 3C for charging. If the potential of the negative electrode relative to the reference electrode is still lower than 0V, continue to reduce the current for charging, and the current is reduced by 0.5C each time until the battery charge reaches 80% SOC. Record the total charging time T, and the fast charging rate = 42 / T.
[0128] (2) Cyclic performance test: the voltage range is set to 2.5V~4.4V, the cycle system is set to: 1C / 1C, the charging process: 1C constant current charging to 4.4V, constant voltage until the current is less than 0.05C, the discharge process: 1C constant current discharge to 2.5V; the first cycle discharge capacity is recorded as the initial capacity, and the test is terminated when the capacity drops to 80% of the initial capacity in a cyclic charge and discharge cycle, and the number of cycles is recorded.
[0129] The test results of the above tests are shown in Table 1.
[0130] Table 1
[0131] 10% SOC~80% SOC fast charge rate / C Number of cycles at which the capacity retention rate is 80% / cycle Example 1 3 2000 Comparative Example 1 2.2 1200 Comparative Example 2 2.4 1400 Comparative Example 3 2.5 1400 Comparative Example 4 3 1350
[0132] It can be seen from the data in Table 1 that the fast charging rate and the number of cycles of the battery containing the negative electrode sheet prepared in Example 1 are significantly improved compared with the batteries containing the negative electrode sheets prepared in Comparative Examples 1 to 4, that is, the fast charging capability and the cycle performance of the battery containing the negative electrode sheet prepared in Example 1 are greatly improved. This shows that in the present application, since the active layer in the negative electrode sheet is three layers, wherein the first active layer includes graphite and silicon-based materials, which can exert a higher gram capacity, and the third active layer includes graphite with high conductivity, has a higher fast charging capability, and is conducive to forming a stable and dense solid electrolyte interface film at the interface between the negative electrode sheet and the electrolyte to ensure the cycle performance of the battery, by arranging a second active layer including soft carbon and / or hard carbon between the first active layer and the third active layer, the active ions (such as lithium ions or sodium ions) are embedded and released in the soft carbon and / or hard carbon at a fast speed, so that the second active layer can be used as a fast ion conductor layer, which is convenient for the transmission of active ions and avoids the interlayer lithium precipitation phenomenon between the first active layer and the second active layer, thereby ensuring the energy density of the battery cell while improving the cycle performance and fast charging performance of the battery cell.
[0133] From the data comparison of Comparative Example 2, Comparative Example 3 and Example 1 in Table 1, it can be seen that the negative electrode sheet of Comparative Example 2 includes two active layers, and lacks the soft carbon and / or hard carbon active layer located between the two active layers relative to Example 1, and the fast charging rate and cycle number of the corresponding battery cell are also significantly lower than the fast charging rate and cycle number of the corresponding battery cell in Example 1; the negative electrode sheet of Comparative Example 3 includes two active layers, and lacks the graphite active layer located in the outermost layer relative to Example 1, and the fast charging rate and cycle number of the corresponding battery cell are also significantly lower than the fast charging rate and cycle number of the corresponding battery cell in Example 1. This shows that it is difficult to effectively improve the cycle performance and fast charging performance of the battery cell by forming a single layer of active layer containing graphite or a single layer of active layer containing hard carbon on the surface of the active layer containing graphite and silicon oxide materials.
[0134] From Table 1, it can be seen from the data comparison between Comparative Example 4 and Example 1 that the negative electrode sheet of Comparative Example 4 includes three active layers. Compared with Example 1, the active layers located on the surface of the negative electrode current collector are the same, but the active layer located in the middle contains graphite, and the active layer located in the outermost layer includes hard carbon. Although the fast charging rate of the battery cell corresponding to Comparative Example 4 is at a relatively high level, the number of cycles of the battery cell is low, that is, the cycle performance of the battery cell is poor. This further shows that in the present application, the first active layer, the second active layer and the third active layer are stacked in sequence to effectively improve the cycle performance and fast charging performance of the battery cell.
[0135] It should be noted that the negative electrode sheet embodiments, negative electrode sheet preparation method embodiments and battery embodiments provided in the present application belong to the same concept; the technical features in the technical solutions recorded in the embodiments can be arbitrarily combined without conflict.
[0136] It should be understood that the above embodiments are exemplary and are not intended to include all possible implementations. Various modifications and changes may be made on the basis of the above embodiments without departing from the scope of the present disclosure. Similarly, the various technical features of the above embodiments may be arbitrarily combined to form other embodiments of the present invention that may not be explicitly described. Therefore, the above embodiments only express several implementations of the present invention and do not limit the scope of protection of the patent of the present invention.
Claims
1. A negative electrode sheet, characterized in that: include: current collector; An active layer, disposed on at least one side surface of the current collector, the active layer comprising a first active layer, a second active layer and a third active layer sequentially stacked on the current collector; The material of the first active layer includes graphite and silicon-based material, the material of the second active layer includes soft carbon and / or hard carbon, and the material of the third active layer includes graphite.
2. The negative electrode sheet according to claim 1, characterized in that: The material of the first active layer further includes a first binder, the material of the second active layer further includes a second binder, and the material of the third active layer further includes a third binder; the negative electrode sheet satisfies at least one of the following characteristics: (1) The first binder includes at least two of sodium carboxymethyl cellulose, styrene-butadiene rubber, and polyacrylic acid binders; (2) the second binder comprises at least two of sodium carboxymethyl cellulose, styrene-butadiene rubber, and polyacrylic acid binders; (3) The third binder includes at least two of sodium carboxymethyl cellulose, styrene-butadiene rubber, and polyacrylic acid binders; (4) The mass percentage of the first binder in the first active layer is 2.5% to 10%; (5) The mass percentage of the second binder in the second active layer is 2% to 6%; (6) The mass proportion of the third binder in the third active layer is 1.5% to 3%.
3. The negative electrode sheet according to claim 1, characterized in that: The material of the first active layer further includes a first conductive agent, the material of the second active layer further includes a second conductive agent, and the material of the third active layer further includes a third conductive agent; the negative electrode sheet satisfies at least one of the following characteristics: (1) The first conductive agent includes at least one of carbon black, carbon nanotubes, graphene, and acetylene black; (2) the second conductive agent includes at least one of carbon black, carbon nanotubes, graphene, and acetylene black; (3) The third conductive agent includes at least one of carbon black, carbon nanotubes, graphene, and acetylene black; (4) the mass proportion of the first conductive agent in the first active layer is greater than the mass proportion of the second conductive agent in the second active layer, and greater than the mass proportion of the third conductive agent in the third active layer; (5) The mass proportion of the second conductive agent in the second active layer is greater than the mass proportion of the third conductive agent in the third active layer.
4. The negative electrode sheet according to any one of claims 1 to 3, characterized in that: The negative electrode sheet satisfies at least one of the following characteristics: (1) The silicon-based material includes at least one of silicon dioxide, silicon carbon, and silicon; (2) In the first active layer, the mass proportion of the silicon-based material in the mixture of the graphite and the silicon-based material is greater than 0 and less than or equal to 90%; (3) The surface density of the negative electrode sheet is 4.54 mg / cm 2 ~12.34mg / cm 2 ; (4) The thickness of the first active layer is 10 μm to 70 μm; (5) The thickness of the second active layer is 5 μm to 20 μm; (6) The thickness of the third active layer is 8 μm to 40 μm.
5. A method for preparing a negative electrode sheet, characterized in that: The following steps are involved: S1: preparing a first slurry, a second slurry and a third slurry, wherein the first slurry comprises a first active material, the first active material comprises graphite and a silicon-based material, the second slurry comprises a second active material, the second active material comprises soft carbon and / or hard carbon, and the third slurry comprises a third active material, the third active material comprises graphite; S2: coating the first slurry, the second slurry and the third slurry on at least one side surface of the current collector, and drying to obtain a first active layer, a second active layer and a third active layer sequentially stacked on the current collector; the material of the first active layer includes the first active material, the material of the second active layer includes the second active material, and the material of the third active layer includes the third active material.
6. The method for preparing a negative electrode sheet according to claim 5, characterized in that: The mass proportion of the silicon-based material in the first active material is greater than 0 and less than or equal to 90; and / or the silicon-based material includes at least one of silicon monoxide, silicon carbon, and silicon.
7. The method for preparing a negative electrode sheet according to claim 5, characterized in that: The step S1 of preparing the first slurry comprises: The first active material, the first binder and the first conductive agent are mixed to prepare the first slurry; the mass ratio of the first active material, the first binder and the first conductive agent is (85-97): (2-10): (1-5).
8. The method for preparing a negative electrode sheet according to claim 5, characterized in that: The step S1 of preparing the second slurry comprises: The second active material, the second binder and the second conductive agent are mixed to prepare the second slurry; the mass ratio of the second active material, the second binder and the second conductive agent is (96-98): (1.5-3): (0.5-1).
9. The method for preparing a negative electrode sheet according to claim 5, characterized in that: The preparation of the third slurry in step S1 includes: The third active material, the third binder and the third conductive agent are mixed to prepare the third slurry; the mass ratio of the third active material, the third binder and the third conductive agent is (96-98): (1.5-3): (0.5-1).
10. A battery, characterized in that: A negative electrode sheet comprising the negative electrode sheet described in any one of claims 1 to 4 or a negative electrode sheet prepared by the preparation method described in any one of claims 5 to 9.
Citation Information
Patent Citations
Pole piece of negative electrode and preparation method of pole piece as well as lithium-ion battery using negative electrode
CN106058154A
Lithium ion battery hierarchical composite negative electrode and preparation method and application thereof
CN113921758A
Negative plate, preparation method thereof and lithium ion battery
CN115566136A
Negative plate, preparation method of negative plate and battery
CN115663114A
Negative pole piece as well as preparation method and application thereof
CN116581271A